Educação escolar indígena no estado do Tocantins: uma trajetória histórica do curso de capacitação ao curso de formação do magistério indígena - Muniz, Simara de Sousa (2018)
In this work we present the results of a research on the Indigenous Education of the State of Tocantins. The objective was to carry out a study on Indigenous School Education in the state of Tocantins, identifying the historical trajectory of the training course and the training of indigenous teachers. We work from qualitative research procedures, as well as bibliographical and documentary research. The theoretical bases deal with Indigenous School Education; Indigenous Teaching; Training of Indigenous Teachers. Thus, the theoretical bases that support our research contemplate for Indigenous Education, we use the theories of: RCNEI (1988), Albuquerque (1999, 2007, 2011, 2013, 2015), Grupioni (2001, 2006), Lopes da Silva (2001) ), Lopes da Silva and Grupioni (2001). Almeida (2011, 2012, 2013, 2015), D'Angeles (2010, 2013), Lima (2012). On Indigenous Education in Tocantins, Albuquerque (2007, 2008, 2011), Almeida (2011, 2015). About the Indigenous Magisterium in Tocantins: Braggio (1992, 1998, 2002), Albuquerque (2007). On the Training of Indigenous Teachers: Albuquerque (2011, 2012), Maher (2005; 2006; 2010), Grupioni (2006), RCNEI (1988), among others. In addition to these, we consulted indigenous and indigenous education policies, FUNAI (2010, 2016), MEC / PNE (2010, 2013), SEDUC (2016), Grupioni (2001) and Barros (2004), presenting a framework for identifying its impact on our education system. The results present a scenario in which the Indigenous Teachers of the State of Tocantins seek a formation that allows the construction of a truly indigenous school, where the knowledge and practices of the indigenous universe are realized. In addition, the Secretariat of Education of Tocantins SEDUC maintains a continuing education program, an Indigenous Magisterium, in which teachers from the various schools of the indigenous villages of the state can improve their pedagogical practice, seeking, through intercultural relations, an understanding of the place they occupy in Brazilian society, starting from School Education.